Minimally Invasive Surgery for Intracochlear Schwannoma Removal and Simultaneous Cochlear Implantation - Bento,Ricardo Ferreira (2016)
Abstract Introduction Hearing preservation has not yet been reported in patients undergoing resection of intracochlear schwannomas. This study describes a minimally invasive procedure for intracochlear schwannoma resection with simultaneous cochlear implantation that resulted in good hearing. Objective This study aims to describe a minimally invasive procedure for intracochlear schwannoma resection with simultaneous cochlear implantation. Data Synthesis The technique described in this study was developed for a 55-year-old male with a 20-year history of bilateral progressive hearing loss and tinnitus that had a mass in the left apical turn of the cochleameasuring 0.3 cm. Surgery accessed the apical turn of the cochlea. We performed mastoidectomy and posterior tympanotomy and removed incus and tensor tympani muscle to expose the cochlear apex. The tumor was identified and completely resected. After the cochleawas anatomically preserved, it was implanted with a straight electrode via round window insertion. The histopathological examination confirmed intracochlear schwannoma. Speech perception test revealed 100% speech recognition with closed sentences and the average audiometric threshold (500 to 2000 Hz) was 23 dB. Conclusion Our technique led to rehabilitation of the patient and improved hearing without damaging the intracochlear structure, making it possible to perform CI in the same procedure with good results.